(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
Carbon is one of the versatile materials used in modern life for human welfare. It has a wide range of applications such as drug delivery, coatings, energy generation and storage, gas separation, water purification, sensor fabrication, and catalysis. Most of the widely used carbon materials are graphene and carbon nanotubes. Nonrenewable precursors (e.g., natural gas), toxic chemicals, and complex synthesis methods are often required for their preparation, limiting their wide practical applications. Besides these, biomass-derived carbons are attractive materials as they can be prepared simply from renewable biomass. However, their practical applications’ success partially depends on their properties like size, shape, porosity, and presence of heteroatoms, which can be controlled by selecting the proper type of biomass, activating agent, and preparation method. It is noted that different species of plants have different chemical compositions and textures. This mini-review summarizes our group’s recent sophisticated developments in agricultural-bio-waste-derived carbonaceous materials, including nanomaterials for electrocatalytic water splitting, electrochemical sensors, supercapacitors, water splitting, water treatment, gas separation, and enhance oil recovery. This offers valuable insights and essential guidelines towards the future design of agro-waste derived carbonaceous materials in various applications. Bangladesh J. Plant Taxon. 27(2): 467-478, 2020 (December)